(untitled) (Jurnal Ilmiah Metansi (Manajemen dan Akuntansi), 2025)
This study aims to determine the impact of the Covid-19 pandemic from 2019 to 2020 on the banking sector in Indonesia. In this study, a type of comparative research between before and during the covid pandemic used data analysis techniques of paired-sample t-test and Wilcoxon test. And the data source uses secondary data obtained using library research techniques. In the research population, as many as 20 banks were obtained, which were then purposive sampling techniques to 6 banks. The results of the study found that of the five (5) variables, only one had a significant impact, namely on the Return On Asset ratio and for the others did not have a significant impact. This means that the financial performance of banks in Indonesia, even though hit by the Covid-19 pandemic, can still survive. It shows that bank management in dealing with risks that occur in the future can overcome them.